Odpowiedzi

2009-10-31T16:13:22+01:00
W(x) = (x+3)/(x²+4x+m)

a) dla m=4
W(x) = (x+3)/(x²+4x+4)=(x+3)/(x+2)²
D = R - {-2}

b) dla m=3
W(x) = (x+3)/(x²+4x+3)=x³+4x²+3x+3x²+12x+9=x³+7x²+15x+9

x=2√3

W(2√3) = (2√3)³+7*(2√3)²+15*(2√3)+9=93+54√3

rozloz wielomian na czynniki:
W(x)=x⁶ +3x⁵-x³-3x² = 3x²(x³-1)+x³(x³-1) = (x³-1)(3x²+x³) = (x-1)(x²+x+1)x²(3+x) = x²(x-1)(x+3)(x²+x+1)
1 4 1
2009-10-31T16:22:03+01:00
(x+3)/ (x²+4x+m)
a.
x²+4x+4=0
a=1 b=4 c=4
delta=b²-4ac
delta=16-16
delta=0
x=-b/2a
x=-4/2
x=-2
D=R\{-2}

b.
(x+3)/(x²+4x+3)
(2√3+3)/([2√3]²+4*2√3+3) =
(2√3+3)/(12+8√3+3) =
(2√3+3)/(8√3+15) = ¼√3+⅕


Rozłóż wielomian na czynniki
x⁶ +3x⁵-x³-3x² = x³(x³-1)+3x²(x³-1) = (x³-1)(x³+3x²) = x²(x+3)(x+1)(x+1)(x-1)

Nie jest na 100% pewna co do tego punktu b z zadania pierwszego
1 5 1